The rise of noncommunicable diseases in Latin America and the Caribbean: Challenges for public health policies - Anauati, Maria Victoria (2015)
The health landscape in Latin America and the Caribbean is changing quickly. The region is undergoing a demographic and epidemiological transition in which health problems are highly concentrated on noncommunicable diseases (NCDs). In light of this, the region faces two main challenges: (1) develop cost-effective policies to prevent NCD risk factors, and (2) increase access to quality healthcare in a scenario in which a large share of the labor force is employed in the informal sector. This paper describes both alternative interventions to expand health insurance coverage and their trade-off with labor informality and moral hazard problems. The paper also focuses on obesity as a case example of an NCD, and emphasizes how lack of knowledge along with self-control problems would lead people to make suboptimal decisions related to food consumption, which may later manifest in obesity problems.